Laboratory production of cattle embryos [ - Gordon, Ian , 1928- (Biotechnology in agriculture series, 2003)
This new edition reviews advances in embryo production technology, based on some 3500 reports that have appeared since the first edition was published in 1994. The work emphasizes the common ground between those working in cattle and human embryology.